Influences of Shifted Vegetation Phenology on Runoff Across a Hydroclimatic Gradient - Chen, Shouzhi; Fu, Yongshuo H.; Geng, Xiaojun; Hao, Zengchao; Tang, Jing; Zhang, Xuan; Xu, Zongxue; Hao, Fanghua (Frontiers in Plant Science, 2022)
Climate warming has changed vegetation phenology, and the phenology-associated impacts on terrestrial water fluxes remains largely unquantified. The impacts are linked to plant adjustments and responses to climate change, and can be different at different hydroclimatic regions. Based on remote sensing data and hydrological station observed river runoff from six river basins across a hydroclimatic gradient from northeast to southwest in China, the relative contributions of the vegetation (including spring and autumn phenology, growing season length and gross primary productivity) and climatic factors affecting the river runoffs over 1982-2015 were investigated by applying grey relational analysis. We found that the average growing season lengths in humid regions (190 241 days) were longer than that in semi-humid regions (186 192 days), and the average growing season lengths were consistently extended by 4.8 13.9 days over 1982-2015 period in six river basins. The extensions were mainly linked to the delayed autumn phenology in the humid regions, and to advanced spring phenology in the semi-humid regions. Across all river basins, the grey relational analysis results showed that precipitation (r = 0.74) and soil moisture (r = 0.73) determine the river runoffs, and the vegetation factors especially the vegetation phenology also affected the river runoffs (spring phenology: r = 0.66; growing season length: r = 0.61; autumn phenology: r = 0.59), even larger than the contribution from temperature (r = 0.57), but its relative importance are climatic regions dependent. Interestingly, the spring phenology is the main vegetation factor in the humid region for runoffs reduction, while both spring and autumn growth phenology are the main vegetation factors in the semi-humid region, on account of large autumn phenology delay and less water supply capacity in spring amplifies the effect of spring phenology advance. This paper reveals diverse linkages between climatic and vegetation factors, and runoff in different hydroclimatic regions, and provides insights that vegetation phenology influences the ecohydrology process largely depending on the local hydroclimatic conditions, which improve our understanding of terrestrial hydrological responses to climate change.